2003
DOI: 10.1590/s0085-56262003000200005
|View full text |Cite
|
Sign up to set email alerts
|

Larval endoparasitoids (Hymenoptera) of frugivorous flies (Diptera, Tephritoidea) reared from fruits of the cerrado of the State of Mato Grosso do Sul , Brazil

Abstract: ABSTRACT. This paper presents a five years survey of endoparasitoids obtained from the larvae of frugivorous Tephritidae and Lonchaeidae flies. The insects were reared from cultivated and wild fruits collected in areas of the cerrado in the State of Mato Grosso do Sul, Brazil. The flies obtained from 14 host fruit species were eight Anastrepha species, Ceratitis capitata (Wiedemann, 1824) (Tephritidae); Dasiops sp. and Neosilba spp. (Lonchaeidae). Eleven parasitoid species were collected: Braconidae -Asobara a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 11 publications
3
21
0
14
Order By: Relevance
“…The location, diversity and quantity of native hosts in the areas where the traps were installed were probably the factors that contributed to the predominance of species of Anastrepha and low capture C. capitata index, similar to the results obtained by Uramoto et al (2004 (Wied.). Anastrepha fraterculus presented the highest population level in the region.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…The location, diversity and quantity of native hosts in the areas where the traps were installed were probably the factors that contributed to the predominance of species of Anastrepha and low capture C. capitata index, similar to the results obtained by Uramoto et al (2004 (Wied.). Anastrepha fraterculus presented the highest population level in the region.…”
Section: Resultssupporting
confidence: 84%
“…The highest percentage of capture of A. fraterculus is here related to the fact of its poliphagous behavior and the existence of many species of Myrtaceae (its preferred host) in sampled areas. Others studies in this region also showed the dominance of this species (Bittencourt et al, 2006a;Dutra et al, 2009;Santos et al, 2008;Santos et al, 2011) and in others regions of Brazil (Araújo et al, 2013;Uramoto et al, 2004Uramoto et al, , 2005.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations